KEPRET KAMALE: KARYA TARI PENGEMBANGAN DARI TARI JAIPONGAN DAN POP DANCE - Dhea Indres Narulita (Joged, 2019)
Kepret Kamale merupakan perpaduan dari kata Kepret yang diambil dari nama gerak tari Jaipongan Jawa Barat, dan Kamale yang dalam bahasa Sunda berarti kemana-mana. Maka jika digabungkan, kedua kata ini menjadi kepret yang kemana-mana. Karya ini menjadi sebuah karya yang memadukan tari Jaipongan dan gerak Pop Dance seperti Waking dan K-pop (Koreanstyle) tetapi tetap berorientasikan pada gerak Kepret. Tipe tarian Kepret Kamale adalah studi dari gerak Kepret tari Jaipongan. Dengan pengembangan gerak dan pengolahan gerak atas kemungkinan- kemungkinan dalam mengembangkan gerak tersebut, misalnya gerak Kepret pada umumnyadigerakkan pada tangan lalu divariasikan ke bagian tubuh lainnya seperti kepala, bahu, dada, badan, lengan, pinggul, pantat, dan kaki, maka akan menghasilkan teknik dan gerak yang baru. Kepret Kamale is Kepret taken from the name of Jaipongan dance movement of West Java and Kamale taken from the Sundanese language which means everywhere. Kepret motion taken from Jaipongan dance movement of West Java which is characteristic of dance that exist in West Java. Kepret motion is varied and then developed with aspects of time, space, and energy. So finding new techniques and moves.However, this dance will still be directed and oriented to Jaipongan dance and combined with Pop Dance movements such as Waking and K-pop (Koreanstyle) but still oriented to Kepret movement according to the ability of the stylist. Dance type KepretKamale is a study of motion Kepret Jaipongan dance. Search and development of motion or possibilities in developing the motion, for example Kepret motion is generally moved on the hands and then varied to other body parts such as head, shoulders, chest, body, arms, hips, buttocks and feet, it will produce techniques and motion the new one.